Reviving Faith: The Dynamic Legacy of HKBP Resort Balige Church - Pinem, Masmedia; Burhanudin, Dede; Cahyadi, Indrawan; Rohanda, Rohanda; Nurjaman, Andri (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2024)
HKBP is one of the largest congregations in the world and has even spread to America and Europe. HKBP in Indonesia is a Christian Church based in Tanah Batak, namely in Tarutung City, North Tapanuli, North Sumatra Province. The main focus of this research is the history of the HKBP Resort Balige church. This research uses a historical research method which has four stages, namely stages heuristics, criticism, interpretation and historiography. The research results show that the history and development of the HKBP Ressort Balige Church began with the arrival of Christian missionaries to Batak Land, then built the HKBP church, which was consecrated as the HKBP Balige church by Ompu Ephorus Pdt. I.L. Nommensen. In its development, the HKBP Balige church developed well; this was marked by the social charities around the church, such as hospitals, Schools, universities and a Multi-Purpose Building which functioned as a public service to the surrounding community. The role of the HKBP Church in the social life of the Balige community as a fellowship of believers always requires order and order in the implementation of services. This can be proven by your willingness to be selected as an Elder, Deacon, or Servant on the Development Commission or on the Committee of an activity.